2007
DOI: 10.1007/s00300-007-0325-8
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite analysis reveals genetic differentiation between year-classes in the icefish Chaenocephalus aceratus at South Shetlands and Elephant Island

Abstract: Chaenocephalus aceratus is one of the most abundant Antarctic icefish species in the Atlantic sector and has been a by-catch species in the fishery for mackerel icefish, Champsocephalus gunnari, between the mid-1970s and mid-1980s at South Georgia, South Orkney, and South Shetland Islands. The species became the target of the fishery in particular seasons, such as at South Georgia in 1977/78. In our paper, we report results on genetic differentiation for 11 microsatellite loci in C. aceratus samples collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
2
12
1
Order By: Relevance
“…Although single-loci p-value estimates varied between these 2 methods (Table A1), results revealed significant differences after sequential Bonferroni corrections in all pairwise comparisons (p < 0.0001), except between southern South Shetlands and Elephant Island collected in 2002 (p = 0.10040 from Fisher's test and p = 0.06363 from chi-squared test). This latter result confirmed, after re-codification of allele classes, the previous results of Papetti et al (2007). In addition, the present study revealed: (1) (Manni et al 2004) (Fig.…”
Section: Population Structuresupporting
confidence: 81%
See 4 more Smart Citations
“…Although single-loci p-value estimates varied between these 2 methods (Table A1), results revealed significant differences after sequential Bonferroni corrections in all pairwise comparisons (p < 0.0001), except between southern South Shetlands and Elephant Island collected in 2002 (p = 0.10040 from Fisher's test and p = 0.06363 from chi-squared test). This latter result confirmed, after re-codification of allele classes, the previous results of Papetti et al (2007). In addition, the present study revealed: (1) (Manni et al 2004) (Fig.…”
Section: Population Structuresupporting
confidence: 81%
“…1b, Table 5). In agreement with previously published studies, effective population size (N e ) varied considerably between methods (Fraser et al 2007), with MIGRATE providing the highest estimates (Table 6); the N e values are nevertheless different from previous estimates calculated between cohorts considering drift only (N e = 96 in Papetti et al 2007). In particular, Elephant Island and South Orkney showed higher N e values than before, also when considering the 95% confidence intervals (average from 241.4 to 21 236.39 for EI06 and from 264.00 and 16 491.42 for SO06; Table 6).…”
Section: Gene Flow and Effective Population Sizesupporting
confidence: 76%
See 3 more Smart Citations